2021
DOI: 10.1002/ppul.25671
|View full text |Cite
|
Sign up to set email alerts
|

Protracted respiratory findings in children post‐SARS‐CoV‐2 infection

Abstract: Introduction Although prolonged respiratory symptoms following severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection have been described in adults, data are emerging that children also experience long‐term sequelae of coronavirus disease 2019 (COVID‐19). The respiratory sequelae of COVID‐19 in children remain poorly characterized. In this study we describe health data and respiratory findings in pediatric patients presenting with persistent respiratory symptoms following COVID‐19. Methods This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
82
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(106 citation statements)
references
References 22 publications
11
82
1
Order By: Relevance
“…Pulmonary function was normal in 75% of our participants, including children and adolescents with persistent respiratory symptoms. This finding is in line with the results of Lefkin Dobkin et al, who found primarily normal results on body plethysmography and diffusion capacity for 15 children with ongoing respiratory symptoms ( 9 ). In our cohort, LCI 2.5% , FEV 1 , DLCO, and DLCO/VA had no significant differences between patients and controls.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Pulmonary function was normal in 75% of our participants, including children and adolescents with persistent respiratory symptoms. This finding is in line with the results of Lefkin Dobkin et al, who found primarily normal results on body plethysmography and diffusion capacity for 15 children with ongoing respiratory symptoms ( 9 ). In our cohort, LCI 2.5% , FEV 1 , DLCO, and DLCO/VA had no significant differences between patients and controls.…”
Section: Discussionsupporting
confidence: 91%
“…Bottino et al performed spirometry and diffusion capacity testing in seven children approximately 2 months after recovery from mild SARS-CoV-2 infection and did not detect any abnormalities ( 8 ). Lefkin Dobkin et al came to a similar conclusion in their study, finding primarily normal results on body plethysmography and diffusion capacity testing for 15 children with ongoing respiratory symptoms approximately 3 months after COVID-19 ( 9 ). A case report described ventilation-perfusion inhomogeneities as possible causes of dyspnea in children and adolescents after COVID-19 ( 10 ).…”
Section: Introductionsupporting
confidence: 57%
“… 32 Although spirometry was mostly normal for children with long-term respiratory symptoms after severe SARS-CoV-2 infection, as in this case, PIBO may occur in children with risk factors. 33 Therefore, spirometry testing should be considered early in children with severe COVID-19 who have risk factors for respiratory complications.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that adults and children with established type 1 and type 2 diabetes mellitus, particularly those with Black race, have a higher incidence of diabetic ketoacidosis during COVID-19 illness [6][7][8]. There is mixed evidence in asthma with multiple studies reporting worsening asthma symptoms and rates of hospitalization during COVID-19 illness [9][10][11][12][13] while other studies report a protective or neutral effect [14][15][16][17][18]. Obesity predisposes children to increased severity of COVID-19 and is a risk factor for critical illness in adolescents with COVID-19 [19,20].…”
Section: Introductionmentioning
confidence: 99%